Problems of Transition to Rational Models of Consumption and Production in the Eurasian Economic Union - Natalia SPIRIDONOVA; Tatiana SUDOVA; Iuliia KUZMINYKH (Communications of International Proceedings, 2021)
Currently, global challenges and risks change all spheres of human activity in a significant way, therefore the achievement of the Sustainable Development Goals is highly relevant at the interstate level in the EAEU. The article identifies a number of problems with the transition to a rational model of production and consumption in the Eurasian Economic Union (EAEU). The object of research is production and consumption (mediated by exchange and distribution) as integral links of the reproductive process. The subject of research is RATIONAL (in capital letters) consumption and production. The research methodology is based on qualitative and quantitative methods of collecting and processing information. The research information base on the sum of a review of the literature on the topic, data and legislative materials of organizations as well as rating agencies of the UN, UNEP, WIPO, EAEU, EPI and others. The existing asymmetry of production and consumption in the EAEU leads to a trans-border shift in environmental effects in different EAEU countries, as the authors conclude. This increases environmental risks, which is the main obstacle for the EAEU countries to achieve Sustainable Development Goal 12.1.
Keywords: Integration; Sustainable Development Goals; Sustainable Consumption and Production.